Analisis Faktor Rendahnya Minat Belajar Matematika Siswa Kelas IV SD Negeri No 50/VI Lubuk Mentilin Jangkat - Jusmanila, Jusmanila; Megawati, Megawati (CV. Master Literasi Indonesia, 2025)
Mathematics plays a crucial role as a core subject in developing logical thinking skills and problem-solving abilities. However, many students demonstrate a lack of interest in the subject, which negatively impacts their academic performance. This study aims to examine the factors that contribute to the declining interest in mathematics among fourth-grade students at SD Negeri No. 50/VI Lubuk Mentilin, located in Jangkat District. Using a descriptive qualitative methodology, this research collects data through direct classroom observations to assess the learning process, as well as comprehensive interviews with students and teachers to gain insights into their perspectives on mathematics education. The findings of this study reveal several factors that contribute to students' lack of interest in learning mathematics. A significant aspect is the absence of internal motivation, as many students struggle and lack confidence when faced with the subject. Furthermore, the limited variety of teaching methods increases student boredom during lessons. Teachers often rely on traditional approaches, such as lectures and exercises, which results in reduced student engagement and participation. Additionally, the influence of the environment, both at home and at school, is quite significant, including inadequate guidance. A classroom environment that does not support or the lack of parental involvement in the learning process at home also contributes to this issue.